2013
DOI: 10.1177/1069397113510272
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Female Body Size and Shape in China, Hong Kong, and the United Kingdom

Abstract: Photographs of 50 women were rated for attractiveness, health, and fertility recorded by four sets of participants-Rural-Chinese (n = 50), Chinese participants in Hong Kong (n = 50), Chinese participants living in the United Kingdom (n = 50), and participants self-identifying as "Caucasian" living in the United Kingdom. The results suggest that a polynomial function of Body Mass Index (kg/m 2 ) is the best predictor of all three judgments in all four observer groups. In contrast, shape cues, such as the waist-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 79 publications
(169 reference statements)
2
9
0
Order By: Relevance
“…These findings were in agreement with previous observation that female bodies with a low but healthy BMI often attract the highest attractiveness ranking (Mo et al, 2013;Tovée et al, 1998). The fact that size 6 was rated similarly to size 14 suggested that thinner is not necessarily more attractive.…”
Section: Discussionsupporting
confidence: 93%
“…These findings were in agreement with previous observation that female bodies with a low but healthy BMI often attract the highest attractiveness ranking (Mo et al, 2013;Tovée et al, 1998). The fact that size 6 was rated similarly to size 14 suggested that thinner is not necessarily more attractive.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, it is conceivable that this might lead to a difference in how bodies were judged. However, a comparison of data collected with the same set of images using print-outs of body photographs as well as computer displays found no differences in the pattern of ratings when the two modes of presentation were compared (Mo et al 2014). The current results also suggest that there is no significant difference between using a 2-AFC versus a VAS method of recording attractiveness judgements.…”
Section: Discussionmentioning
confidence: 47%
“…Men also report greater attraction towards pictures of women with low WHRs (Dixson, Li, & Dixson, 2010;Mo et al, 2014;Singh, 1993Singh, , 2002Suschinsky, Elias, & Krupp, 2007). Given the relation between women's sexual interest and their partner's physical attractiveness, and attractiveness and women's WHRs, it seems that manipulating the WHRs of the women pictured could be used to test whether heterosexual women's viewing times for female pictures are associated with the perceived attractiveness of those pictures and whether their viewing time patterns are gender-specific or not; this was the first goal of the present research.…”
Section: The Role Of Waist-to-hip Ratio and Menstrual Cycle Phasementioning
confidence: 99%